Foreword - Abd Rahim, Alhan Farhanah (Unit Penerbitan Pke, 2025)
It is with great pleasure and pride that I present this edition of the PKE Bulletin, E Waves, a platform that encapsulates the vibrant spirit, resilience, and achievements of our academic community. This publication reflects not only the milestones we have reached but also the aspirations that continue to drive us forward in the field of Electrical Engineering. As we navigate the ever-evolving landscape of engineering education, research, and industr y collaboration, the role of communication and documentation becomes increasingly vital. The PKE Newsletter ser ves as a testament to the collective efforts of our staff, students, and partners, highlighting innovations, academic excellence, outreach initiatives, and the human stories behind every success.